Moral injuries : a novel - Watson, Christie (Harper, an imprint of HarperCollinsPublishers, 2024)
"From the bestselling author of The Language of Kindness comes a high-stakes literary thriller following three women who have been best friends since medical school, whose twenty-five-year-old secret threatens to blow open when their teenaged children find themselves in an eerily similar situation"--